Express-method of sportsmen’s psychological tune-up - Omelyanenko, V.I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to elaborate express-method of autosuggestion for neurotic reactions relieving and sportsmen’s psychological tune-up. Material : 20 senior dancers participated in the research. The research was held 2 times a week within 4 months. The procedures with specially selected physical exercises and autosuggestion influence before training in sports dances were applied in the experimental group guided by psychotherapeutist. Mechanism of the short-time abashment or stupefaction of the testee was taken as a basis. It was achieved by way of the sportsmen’s attempt to determine quickly surfaces of the parts of the body in contact or concentration of attention on the feeling during physical exercise. Results : in the experimental group it was necessary 10-20 sessions for neurotic reactions relieving. Psychological make-up for training was achieved within 1-5 sessions. Short-time improvement of the psychological condition in the control group arrived only after 30-60 minutes of training in sports ball dances. Conclusion : using the elaborated express-method of suggestion it’s possible to effect psychological tune-up of sportsmen for training sessions and competitions. The method of autosuggestion elaborated by us is more effective than impact of the dance-motion therapy upon the organism. It is possible to use the offered method for sportsmen’s neurotic reactions relieving and for make-up for training sessions and competition.